2000
DOI: 10.1542/peds.106.4.e50
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic Fitness, Not Energy Expenditure, Influences Subsequent Increase in Adiposity in Black and White Children

Abstract: ABSTRACT. Background. Low levels of energy expenditure and aerobic fitness have been hypothesized to be risk factors for obesity. Longitudinal studies to determine whether energy expenditure influences weight gain in whites have provided conflicting results. To date, no studies have examined this relationship in blacks or whether aerobic fitness influences weight gain in white or black children.Methods. One hundred fifteen children, 72 white (55 girls and 17 boys) and 43 black (24 girls and 19 boys) were recru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
156
0
4

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(171 citation statements)
references
References 34 publications
11
156
0
4
Order By: Relevance
“…Although testing was completed throughout the school day, the maximal nature of the testing means that there is unlikely to be any effect from circadian variation in VO 2 uptake kinetics (40) . Physical activity levels may influence aerobic fitness; however, it has been shown that aerobic fitness is independently associated with adiposity in children (32) and therefore the aim of the present study was to investigate fitness rather than physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…Although testing was completed throughout the school day, the maximal nature of the testing means that there is unlikely to be any effect from circadian variation in VO 2 uptake kinetics (40) . Physical activity levels may influence aerobic fitness; however, it has been shown that aerobic fitness is independently associated with adiposity in children (32) and therefore the aim of the present study was to investigate fitness rather than physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…25 Thus, the behavioural component of activity may not be captured when PAEE is measured by the DLW method, which may then explain the nonsignificant prospective associations previously observed between activity energy expenditure and gain in FM. [15][16][17][18][19] The impact of exercise intensity on change in body composition is equivocal. [20][21][22][23] Our results suggest that change in overall activity, but not change in any of the subcomponents of activity, is inversely associated with change in FM.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies incorporating an objective measure of PA have been unable to demonstrate a prospective association between PA or PAEE and change in BW or FM. [15][16][17][18][19] One recent study has suggested a prospective association between PA and change in FM but this association was modified by age. 20 Furthermore, the potential impact of exercise intensity on change in BW and FM remains elusive, [21][22][23][24] and it is not known which if any of the subcomponents of free-living PA contributes more to change in BW and FM.…”
Section: Introductionmentioning
confidence: 99%
“…As low fitness is associated with high fatness [7][8][9][10] and low physical activity, 11 the increasing prevalence of obesity and of the proportion of children leading sedentary lifestyles suggest that overall fitness levels may have fallen. Hence, as fitness is an important component of metabolic health [12][13][14][15][16] and a strong independent predictor of premature death, 17 identifying changes in fitness levels among children during the 'obesity epidemic' could indicate the need for interventions to improve fitness in this age group.…”
Section: Introductionmentioning
confidence: 99%